Strengthening the tax system to reduce inequalities and increase revenues in South Africa - Fall, Falilou (OECD Publishing, 2022)
The Covid-19 crisis has exacerbated the already deteriorating fiscal situation in South Africa. The current consolidation strategy, based on spending cuts and reprioritisation of spending items, has reached its limits and is insufficient to stabilise the debt ratio in the medium term and fund unmet public services needs. The tax-benefit system needs to be redesigned to create fiscal space in the years to come to finance growth-enhancing reforms and to reduce inequalities. The challenge is to generate additional revenues without generating inefficiencies or exacerbating inequality. Income taxes represent around half of total tax revenues, but are levied on small tax bases, partly reflecting the unequal distribution of income. Only the value-added tax has a relatively broad basis combined with a moderate tax rate. There is some scope to raise revenues further while reducing existing tax distortions, notably by broadening the base of corporate and personal income taxes, as well as consumption taxes. Taxes with a less harmful impact on growth, such as property taxes, are limited by the inefficient municipal rates system. There remains scope to further increase environmentally-related taxes
Keywords: Economics; South Africa